2021
DOI: 10.3390/cancers13184661
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Hormones Modulate Macrophage Inflammatory Responses

Abstract: Macrophages are phagocytotic leukocytes that play an important role in the innate immune response and have established roles in metabolic diseases and cancer progression. Increased adiposity in obese individuals leads to dysregulation of many hormones including those whose functions are to coordinate metabolism. Recent evidence suggests additional roles of these metabolic hormones in modulating macrophage inflammatory responses. In this review, we highlight key metabolic hormones and summarise their influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 302 publications
(357 reference statements)
0
4
0
2
Order By: Relevance
“…On the other hand, estrogens act via ERα to determine an increase in M2 gene expression and polarization [ 32 ], although E 2 administration does not affect their concentrations [ 31 ] ( Table 1 ).…”
Section: Innate Immune Cellular Componentsmentioning
confidence: 99%
“…On the other hand, estrogens act via ERα to determine an increase in M2 gene expression and polarization [ 32 ], although E 2 administration does not affect their concentrations [ 31 ] ( Table 1 ).…”
Section: Innate Immune Cellular Componentsmentioning
confidence: 99%
“…GLP-1R was detected in mouse and human macrophages, neutrophils, eosinophils, and lymphocytes. 41–45 Studies have shown that GLP-1 and its receptor agonists not only inhibit the levels of total cells, neutrophils, macrophages, eosinophils, lymphocytes, TNF-α, IL-4, IL-5 and IL-13 in mouse alveolar lavage fluid 46 but also mediate anti-inflammatory effects through stress-activated protein kinase (JNK) inhibition, signal transducer and activator of transcriptional activator protein 3 (STAT3) activation and cAMP/PKA/NF-κB signaling pathways, reducing the release of pro-inflammatory markers (iNOS, IL-1β, IL-6, TNF-α and monocyte chemotactic protein-1 (MCP-1), MMP-2, MMP-9, ROS) and increasing the release of anti-inflammatory markers (IL-10, mannose receptor-1 (MRC-1), arginine-1 (Arg-1) release as well as prostaglandin E2 (PGE2) and cyclooxygenase 2 (COX2) mRNA and COX2 protein levels, 42 , 46 thereby achieving a reduced inflammatory response. GLP-1 reduced the number of CD3 + T lymphocytes, F4/80 + macrophages and CD11b + macrophages in the blood of obese and COPD mice and reduced the size of emphysema in mice.…”
Section: The Role Of Glp-1ras In Copdmentioning
confidence: 99%
“…Крім того, лептин може стимулювати вироблення прозапальних цитокінів TNFα, резистину, IL-6 та IL-1β, IL-1Ra, IL-10, MCP-1 та MIP-1α та посилюють експресію ліганду CC-хемокіну. Ці ефекти можуть бути опосередковані активацією шляху JAK2-STAT3, а також можуть активувати шляхи проліферації ERK1/2, MAPK P8, JNK, AMPK, PKC і PI3K/Akt [14].…”
Section: Influence Of Testosterone On Inflammatory Processes (Literat...unclassified
“…У даній роботі була зібрана інформація про прямі і непрямі механізми і наслідки впливу тестостерону на продукцію прозапальних і протизапальних медіаторів. Автори[12,13,14, 15, 16,17,18, 19] показують, що тестостерон знижує активність запальних процесів, за рахунок негативного впливу на жирову тканину та інгібування синтезу прозапальних цитокінів напряму. А також було частково розглянуто його вплив на метаболічні процеси і його кореляцію з ІМТ.…”
unclassified